Assistive Technology Construction in Fulfilling the Rights of Telecommunication Information for Disabled People in Indonesia - Yani, Ahmad; Julhijah, Ratu; Muliana (Indonesian Journal of Disability Studies, 2023)
The problem of accessibility to information and technology for people with disabilities in Indonesia is one of the state's responsibilities that must be implemented comprehensively. This study aims to determine the state's responsibility in fulfilling disability rights to information and telecommunications in Indonesia and aims to construct the ideal form of fulfillment of disability rights to information and telecommunications through assistive technology models. The research uses a normative-empirical method with a conceptual approach, a statutory approach, and a case approach. The results of the study show: First, the state's responsibility for protecting the rights of persons with disabilities to information and technology has been regulated in Article 28 F of the 1945 Constitution of the Republic of Indonesia and in Law Number 8 of 2016 concerning Persons with Disabilities as many as 13 (thirteen) articles. The regulation contains 8 (eight) substances for regulating the right to information for persons with disabilities. The implementation of these provisions has not run optimally because there are still services that are not friendly to persons with disabilities. Second, efforts to encourage the formation of assistive technology for people with disabilities in the country by referring to the needs of people with disabilities in Indonesia. This can be done by establishing two types of assistive technology for persons with disabilities of school age and above school age by adjusting features and services that are friendly to disabilities.